Mitochondrial dynamics and neurodegeneration - Lu, Bingwei (Springer, 2011)
Mitochondria are essential organelles in eukaryotic cells that control such diverse processes as energy metabolism, calcium buffering, and cell death. Recent studies have revealed that changes in mitochondrial morphology by fission and fusion, a process known as mitochondrial dynamics, is particularly important for the function and survival of neurons. Defects in this process are commonly found in neurodegenerative diseases, offering a new paradigm for investigating mechanisms of neurodegeneration. This is the first book that integrates in one volume such diverse subjects as the genetic control of mitochondrial dynamics, the relationship between mitochondrial dynamics and bioenergetics, the roles of mitochondrial dynamics in apoptosis, axonal transport, mitochondrial quality control, and the contribution of defective mitochondrial dynamics to the pathogenesis of neurodegenerative diseases. Focusing on mitochondrial dynamics and its role in neurodegeneration, this book brings together 32 leading scientists and clinicians from around the world to deliver a comprehensive treatise on all aspects of mitochondrial dynamics, from basic research on its molecular basis to its medical implications. The authors have contributed state of the art chapters on their respective areas of expertise, providing readers interested in mitochondrial biology and mechanisms of neurodegenerative diseases with the most up to date information. This fully illustrated volume -- Presents a comprehensive historical account of discoveries leading to the identification of key molecular players involved in mitochondrial dynamics, emphasizing the role played by model organism genetics. -- Describes the fundamental mechanisms by which mitochondrial dynamics and cellular energy status can reciprocally regulate each other. -- Discusses the regulation and inter-dependence of mitochondrial dynamics and mitochondrial autophagy (mitophagy) in mitochondrial quality control. -- Highlights the importance of mitochondrial dynamics in the timely execution of apoptosis. -- Details the molecular processes that lead to the transport and distribution of mitochondria to neuronal axons and synapses, arguably one of the most important aspects of neuronal physiology -- Presents recent findings on the clinical diversity of diseases caused by mutations in the mitochondrial dynamics machinery, the spectrum of mutations in the mitochondrial fusion genes and the corresponding pathophysiology, and the therapeutic perspectives. -- Summarizes a rapidly growing body of literature focusing on the role of mitochondrial dynamics in the pathogenesis of Parkinson's disease and discusses unresolved controversies in the field in the context of a dynamic network of compensatory responses to mitochondrial stress, dysfunction and injury. -- Highlights the role of aberrant mitochondrial dynamics in the pathogenesis of Alzheimer's disease, and offers a molecular mechanism connecting disease-causing insults and post-translational modification of the mitochondrial fission machinery. -- Discusses the published literature linking mitochondrial dysfunction in Huntington's disease, focusing on the role that defects in mitochondrial dynamics might play in disease pathogenesis. Professor Lu has summarized the problems associated with the nascent but rapidly growing research field of mitochondrial dynamics in neurodegeneration and has been successful in editing a must-read book for students, clinicians, and researchers interested in mitochondria biology, neurobiology, and mechanisms of neurodegenerative diseases.